2016
DOI: 10.4103/2277-9531.184557
|View full text |Cite
|
Sign up to set email alerts
|

Effect of self-instructional module on knowledge about ebola virus disease among Nigerian University students in Bengaluru, India

Abstract: Background:The knowledge about Ebola virus disease (EVD) is very crucial in the response to the recent outbreak and in order to control its spread. This study was conducted to assess the effectiveness of self-instructional module (SIM) in enhancing knowledge of EVD among Nigerian students in Bengaluru, India.Materials and Methods:A pre-experimental study design was employed, and a simple random sampling technique was used to select 60 participants. A pretest was conducted with the tool to assess the baseline k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The knowledge increased suddenly which is seen in case for any educational module. 11 The findings are similar to a study conducted in Bengaluru with the same methodology which also found immediate enhancement in knowledge.…”
Section: Discussionsupporting
confidence: 84%
“…The knowledge increased suddenly which is seen in case for any educational module. 11 The findings are similar to a study conducted in Bengaluru with the same methodology which also found immediate enhancement in knowledge.…”
Section: Discussionsupporting
confidence: 84%
“…For instance, a previous study reported that a structured training program was effective in improving students' knowledge about Ebola virus disease. [ 15 ] Also, Galal et al . (2014),[ 16 ] came to similar conclusion in their study conducted in Egypt on the impact of an infection-control program on nurses' knowledge and attitude in PICU at Cairo University hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…From the discussions, it could be seen that the importance of training and retraining cannot be overemphasized for instance; Nwozichi et al . [ 19 ] reported that training program was effective in enhancing knowledge about Ebola virus disease. Suchitra and Lakshim Devi,[ 20 ] in their study conducted in India, on impact of education on various categories of health-care workers' knowledge, attitude, and practices on health-care-associated infection observed that with the progress of time, there was decline in the scores of participants in their study when the postintervention assessment was carried out.…”
Section: Discussionmentioning
confidence: 99%